MURDER OF HUSBAND BY WIFE IN INFIDELITY CASE ACCORDING TO ISLAMIC LAW (ANALYSIS OF THE MEDAN DISTRICT COURT DECISION NUMBER 907/PID.B/2020/PN MDN) - Muarrif el-Ridho Saragih; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (International Journal of Cultural and Social Science, 2025)
This study analyzes the Medan District Court Decision Number 907/Pid.B/2020/PN Mdn, in which the wife, Zuraida Hanum, was sentenced to death for the premeditated murder of her husband due to infidelity. The aim is to assess the judge's reasoning behind this decision from both Islamic and criminal law perspectives. Using a normative juridical approach, this research examines primary, secondary, and tertiary legal materials to understand the application of Islamic law and criminal law in this case. The findings suggest that the judge’s decision was influenced by the heinous nature of the crime and the intent to provide a deterrent effect. From an Islamic law perspective, the death penalty aligns with the retribution for premeditated murder, while criminal law emphasizes justice and public safety. This case highlights the intersection of legal and moral principles in determining appropriate sentencing.